A model-based velocity controller for chaotization of flexible joint robot manipulators: Synthesis, analysis, and experimental evaluations. (29th September 2018) - Miranda-Colorado, Roger; Aguilar, Luis T; Moreno-Valenzuela, J
This article presents a model-based velocity controller able to induce a chaotic motion on n -degrees of freedom flexible joint robot manipulators. The proposed controller allows the velocity link vector of a robot manipulator to track an arbitrary, chaotic reference vector field. A rigorous theoretical analysis based on Lyapunov's theory is used to prove the asymptotic stability of the tracking error signals when using the proposed controller, which implies that a chaotic motion is induced to the robotic system. Experimental results are provided using a flexible joint robot manipulator of two degrees of freedom. Finally, by using Poincaré maps and Lyapunov exponents, it is shown that the behavior exhibited by the robot joint positions is chaotic.